THE EFFECT OF LEADERSHIP, WORK ENVIRONMENT AND EMPLOYEE ENGAGEMENT AS MEDIATION VARIABLES ON THE LEVEL OF EMPLOYEE JOB SATISFACTION (STUDY AT PT. SUCOFINDO SEMARANG BRANCH) - Alsela Suri Trivilanita; Reni Shinta Dewi; Hari Susanta Nugraha (Universitas Diponegoro, 2024)
This research aims to determine the influence of leadership, work environment, and employee involvement as mediating variables on employee job satisfaction levels. The research object is PT. SUCOFINDO Semarang Branch. Research using explanatory type, sampling technique using saturated sample technique. The sample was 64 employees. The data analysis technique uses SmartPLS 3. The research results support the theory of organizational behavior. The research concludes that leadership has a positive and insignificant effect on job satisfaction, leadership has a negative and insignificant effect on employee engagement, the work environment has a positive and insignificant effect on job satisfaction, the work environment has a positive and significant effect on employee engagement, employee engagement as a mediating variable has positive and significant influence on job satisfaction, leadership has a negative and insignificant influence on job satisfaction and employee involvement is not a mediating variable, and the work environment has a positive and significant influence on job satisfaction through employee involvement as a full mediating variable. So, companies must provide good leadership and a comfortable work environment so that employees also feel involved and cause high job satisfaction. Future research: This research can use the employee engagement variable as the dependent variable, or use other variables that can influence job satisfaction or replace the leadership variable with transformational leadership, or can use objects from fellow state-owned companies or government and private agencies.Keyword: leadership; work environment; employee engagement; employee job satisfactionPenelitian ini bertujuan untuk mengetahui pengaruh kepemimpinan, lingkungan kerja, dan keterlibatan karyawan sebagai variabel mediasi terhadap tingkat kepuasan kerja karyawan. Objek penelitian adalah PT. SUCOFINDO Cabang Semarang. Penelitian menggunakan tipe eksplanatori, teknik pengambilan sampel menggunakan teknik sampel jenuh. Sampel sebanyak 64 karyawan. Teknik analisis data menggunakan SmartPLS 3. Hasil penelitian mendukung teori perilaku organisasi. Penelitian menyimpulkan bahwa kepemimpinan berpengaruh positif dan tidak signifikan terhadap kepuasan kerja, kepemimpinan berpengaruh negatif dan tidak signifikan terhadap keterlibatan karyawan, lingkungan kerja berpengaruh positif dan tidak signifikan terhadap kepuasan kerja, lingkungan kerja berpengaruh positif dan signifikan terhadap keterlibatan karyawan, keterlibatan karyawan sebagai variabel mediasi memiliki pengaruh positif dan signifikan terhadap kepuasan kerja, kepemimpinan berpengaruh negatif dan tidak signifikan terhadap kepuasan kerja dan keterlibatan karyawan bukan variabel mediasi, dan lingkungan kerja berpengaruh positif dan signifikan terhadap kepuasan kerja melalui keterlibatan karyawan sebagai variabel full mediasi. Maka, perusahaan harus memberikan kepemimpinan yang baik dan lingkungan kerja yang nyaman agar karyawan juga merasa terlibat dan menyebabkan kepuasan kerja tinggi. Future research penelitian ini dapat menggunakan variabel keterlibatan karyawan sebagai variabel dependen, atau menggunakan variabel lain yang dapat mempengaruhi kepuasan kerja atau mengganti variabel kepemimpinan menjadi kepemimpinan transformasional, atau dapat menggunakan objek sesama BUMN atau instansi pemerintah dan swasta.Kata Kunci: kepemimpinan; lingkungan kerja; keterlibatan karyawan; kepuasan kerja